Bio-Inspired Strategies for Minimizing Distortion in DC-AC Converters - Lucero-Tenorio, Miriam; Aguila-Leon, Jesus (EASI: Engineering and Applied Sciences in Industry, 2023)
The global shift towards sustainable energy sources, such as solar and wind power, underscores the critical role of power converters in renewable energy systems. These converters are essential in converting direct current (DC) generated from renewable sources into alternating current (AC), suitable for use in homes and distribution through the grid. The efficiency and performance of these converters have far-reaching implications for the effective integration of renewable energy into the existing grid infrastructure. However, the classic strategies for controlling and designing power converters exhibit unstable behaviour under varying environmental conditions and changing energy demands. This letter shows some essential concepts and techniques explored in the research field of bioinspired optimisation algorithms and their implementation for the improvement of power converters in the field of renewable energies.
Keywords: Bio-inspired algorithms; power converter; renewable energy; efficiency improvement